Physico-Chemical Quality of Haji Ali Sea Water and Mahalaxmi Coast, South Mumbai, India - Vikrant Deshmukh; Balasaheb Kulkarni (Journal of Indian Fisheries Association, 2022)
Physico-chemical composition of sea water plays an important role in maintaining the biota of sea. The objective of the current study is to characterise the physico-chemical parameters of coastal ecosystem at Mahalaxmi, Haji Ali sea shore, Mumbai, west coast of India. For investigation of water quality, the water samples were collected during high and low tide and analysed to get information on present status of water quality at the site. The study involves investigation of physico-chemical parameters such as temperature, pH, free carbon, BOD, DO, COD, nutrients, hydrogen sulphide and total suspended solids. The results of the presentstudy on physico-chemical characteristic of Mahalaxmi-Haji Ali sea shore indicated seasonal variations. Fluctuation of salinity, dissolved oxygen and nutrients like phosphate and nitrate in shore water were found to be associated with rain fall and subsequent inflow of fresh water into the coastal sea.